Type I MET inhibitors cooperate with PD-1 blockade to promote rejection of hepatocellular carcinoma - Michael A Curran; Joanna Schmidt; Ahmed O Kaseb; Arthur Liu; Madeline Steiner; Ricardo DeAzevedo; Broderick X Turner; Sherwin Newton; Rachel Fleming; Angelica Tolentino (Journal for ImmunoTherapy of Cancer)
Blockade of the immune checkpoints programmed death-1 (PD-1) and cytotoxic lymphocyte antigen 4 has improved outcomes for patients with hepatocellular carcinoma (HCC), yet most still fail to achieve objective clinical benefit. MET plays key roles in both HCC tumorigenesis and immunosuppressive conditioning; however, inhibition of MET causes upregulation of PD-ligand 1 (PD-L1) suggesting the use of these inhibitors in the context of PD-1 blockade. We sought to investigate across the Hepa1-6, HCA-1 and diethylnitrosamine (DEN) models of HCC whether the combination of more specific type I versus more pleiotropic type II MET inhibitors would confer superior outcomes in combination with PD-1 blockade. While MET inhibition demonstrated cooperativity with αPD-1 across all three models, the type I MET inhibitor capmatinib showed optimal activity in combination and statistically significantly outperformed the combination with the type II inhibitor cabozantinib in the αPD-1 refractory DEN model. In both HCA-1 and DEN HCC, the capmatinib and αPD-1 combination enhanced CD8 T cell frequency and activation state while limiting intratumoral myeloid immune suppression. In vitro studies of antigen-specific T cell activation reveal significantly less inhibition of effector cytokine production and proliferation by capmatinib versus by type II or type III MET inhibitors. These findings suggest significant potential for clinical HCC combination studies of type I MET inhibitors and PD-1 blockade where prior trials using type II inhibitors have yielded limited benefit.